Effectiveness of 15-Minute Literacy Movement Before Learning in Improving Students' Reading Skills at State Elementary School 1 Lemahabang - Eriska Aufha Nurani; M.Khozul Huda; Fikriyah Fikriyah (FKIP - Universitas Riau, 2026)
This study aims to analyze the effectiveness of the 15-Minute Literacy Movement Before Learning in improving the reading skills of fourth-grade students at Lemahabang 1 Elementary School. The background of the study is the low reading ability of students, such as weak comprehension of reading content, slow reading speed, and difficulty in conveying information from the text. The research method uses a quantitative approach with an ex post facto design. The research sample consisted of 40 students selected through purposive sampling. Data were collected through questionnaires,observations, interviews, and documentation. Data analysis used normality tests, linearity, simple linear regression, and hypothesis testing with the help of SPSS 22. The results showed that the data were normally distributed, the relationship between linear variables, and a significance value of 0.000 <0.05, t count 33.216 > t table 2.021, and F count 1103.280 > F table 4.10. This proves that the 15-Minute Literacy Movement has a significant influence on students' reading skills. In conclusion, this literacy activity is effectively implemented routinely in elementary schools to form sustainable reading habits.